Strategies for Creating Visual Symbols in Preschool Children (Interdisciplinary Research in Teaching and Learning: New Perspectives and Approaches, 2024)
Preschool children do not draw what they see but rather what they know about the object they wish to draw. These drawings are referred to as symbols. This study investigated how these symbols are created. For the purposes of our research, we grouped the motifs that children transform into symbols during drawing into three categories. Visual examples of the selected motifs were prepared and artistic activities were carried out on their basis. The study found that it was difficult to influence the drawing of spontaneously developed symbols, e.g. a house, a person, an animal or a plant, with direct visual impressions. The similar is true for symbols that emerge later in a child’s development. The study further found that it was possible to influence the drawing of those motifs that children do not develop on their own but only draw when encouraged by adults. Children introduce their own individual visual impressions into these symbols, which vary from one child to another. We developed new terminology for the different subtypes of symbols based on the results of our research.